Analysis of the UtilizationUtilization of a Learning Management System Based on the Independent Curriculum in Physics Education at Sikka Coastal Schools - Hikmatiar, Hamzarudin; Al Farizi, Zakaria; Hamsa, Berlian; Nurlina, Nurlina; Jufriansah, Adi; Jayadin, Jayadin (Universitas Lambung Mangkurat, 2025)
Online learning has emerged as a dominant trend since the onset of the COVID-19 pandemic, leading to significant changes in the educational landscape. Numerous studies have examined using learning management systems (LMS) in educational settings. However, few have addressed the urgency of implementing LMS and the specific challenges coastal schools face. To explore these challenges, the researcher conducted a qualitative, descriptive study to analyze the use of LMS, focusing on a case study of high schools in Sikka Regency. The study involved nine schools, namely SMAN Pemana, MAS Nurwahid Gunung Sari, MAS Muhammadiyah Nangahure, MAS At-Taqwa Beru, SMA Muhammadiyah Maumere, SMAN Magepanda, SMA 1 Talibura, SMKN Talibura, and SMAN 1 Waigete. Data were collected through interviews with nine physics teachers. The research data were then analyzed using NVivo software to obtain quantitative percentages. The findings indicated that all participating schools utilized LMS, with the majority adopting Google Classroom. However, the most significant challenge identified was internet connectivity, with over 50% of the schools acknowledging this issue. Additionally, many students lacked smartphone access, particularly at MAS Muhammadiyah Nangahure, where nearly 2% of students did not own a smartphone, compared to approximately 5% at similar schools. Other challenges included the lack of internet data and limited understanding of technology among students. The most common concern reported by schools was the inflexibility of LMS platforms, particularly concerning their dependence on internet connectivity. For instance, SMAN Pemana noted a 4.8% incidence of issues related to the LMS they were using. Given these obstacles, many schools have turned to alternative solutions to support online learning, such as WhatsApp Groups, which 80% of the schools employ.